Pendampingan Persiapan Kerja Bagi Mahasiswa Tingkat Akhir Vokasi Kampus Wates di Masa Adaptasi Kebiasaan Baru - Voettie Wisataone; Rosidah Rosidah; Nadia Sasmita Wijayanti; Mochamad Hanafi (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
This Community Service Activity aims to provide insight and provision to final-level vocational students at the Wates campus, Kulon Progo, Yogyakarta. The activities include; online seminars and mentoring in making curriculum vitae, job application letters, and preparing for online interviews. The activity was carried out through three stages of activity, namely preparation, implementation and evaluation. Preparation is carried out by conducting a needs survey for final year students regarding work preparation. The implementation is carried out by training and mentoring, using the lecture method, namely through organizing online seminar activities through the Zoom application entitled